Open-label, multicenter, phase III extension study of idalopirdine as adjunctive to donepezil for the treatment of mild-moderate alzheimer’s disease - Frölich, Lutz (Journal of Alzheimer's disease, 2019)
This open-label extension study evaluated the long-term safety and tolerability of idalopirdine 60 mg/day as adjunctive therapy in patients with mild-moderate Alzheimer’s disease (AD). This extension study was a continuation of Studies 1 and 2 of the
Gesehen am 19.11.2019